2019
DOI: 10.1371/journal.pone.0210358
|View full text |Cite|
|
Sign up to set email alerts
|

Ocean acidification at a coastal CO2 vent induces expression of stress-related transcripts and transposable elements in the sea anemone Anemonia viridis

Abstract: Ocean acidification threatens to disrupt interactions between organisms throughout marine ecosystems. The diversity of reef-building organisms decreases as seawater CO 2 increases along natural gradients, yet soft-bodied animals, such as sea anemones, are often resilient. We sequenced the polyA-enriched transcriptome of adult sea anemone Anemonia viridis and its dinoflagellate symbiont sampled along a natural CO 2 gradient in Italy to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 76 publications
1
22
0
Order By: Relevance
“…At present, high-throughput transcriptomics has been applied to 13 types of sea anemones: Anthopleura elegantissima, Anthopleura dowii, Aiptasia pallida, Anemonia sulcata, Anemonia viridis, Cnidopus japonicus, Exaiptasia pallida, Heteractis crispa, Oulactis sp., Megalactis griffithsi, Nematostella vectensis, Stichodactyla helianthus, and Stichodactyla haddoni [18,46,[130][131][132][133][134][135][136][137][138]. There is a growing body of literature using transcriptomics data to study the symbiotic relationship between sea anemones and their symbionts or to study the mechanism of the evolutionary development of sea anemones [131,139,140].…”
Section: Transcriptomics Technologymentioning
confidence: 99%
“…At present, high-throughput transcriptomics has been applied to 13 types of sea anemones: Anthopleura elegantissima, Anthopleura dowii, Aiptasia pallida, Anemonia sulcata, Anemonia viridis, Cnidopus japonicus, Exaiptasia pallida, Heteractis crispa, Oulactis sp., Megalactis griffithsi, Nematostella vectensis, Stichodactyla helianthus, and Stichodactyla haddoni [18,46,[130][131][132][133][134][135][136][137][138]. There is a growing body of literature using transcriptomics data to study the symbiotic relationship between sea anemones and their symbionts or to study the mechanism of the evolutionary development of sea anemones [131,139,140].…”
Section: Transcriptomics Technologymentioning
confidence: 99%
“…However, how the OA-driven responses alter the behaviour of the soft-bodied forms of anthozoans and modify their long-term ecological perspectives is to a large extent unknown. During the last decade, several research groups have reported a negligible (or even positive) impact of OA on the metabolism of sea anemones of species supporting microalgal endosymbionts of Symbiodinium genus due to rapid changes in endosymbionts’ biochemistry and photosynthesis capacity [ 16 , 20 , 40 ]. Nevertheless, the impact of OA on non-symbiotic sea anemones has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Tellingly, anti-apoptotic responses have been reported under decreased pH. Bcl-2 proteins and HSPs, which regulate apoptosis, were upregulated in juvenile A. millepora (Moya et al 2015) and A. viridis (Urbarova et al 2019), suggesting that anti-apoptotic molecules may play an important role in mitigating OA-driven cell loss (Kvitt et al 2011). However, the opposite response was reported by Kaniewska et al (2012) for adult A. millepora, suggesting species-and/or life stage-specific responses, or that longer term exposure to decreased pH may overwhelm these antiapoptotic mechanisms, possibly due to host mitochondrial impairment (Kaniewska et al 2012;Rocker et al 2015;Urbarova et al 2019).…”
Section: Impacts On the Cnidarian-dinoflagellate Symbiosismentioning
confidence: 99%
“…OA has been shown to increase ROS generation and induce oxidative stress in cnidarians (Luz et al 2018;Urbarova et al 2019). Stress responses may include upregulation of HSPs, molecular chaperones, and glucose-regulated proteins involved in ER stress, UPR and suppression of caspase activation (Kaniewska et al 2012;Moya et al 2015;Urbarova et al 2019). These point to upregulation of host innate immune responses and apoptotic processes under combined OA/OW stress (Kaniewska et al 2015;Urbarova et al 2019).…”
Section: Interactive Effects Of Climate Changementioning
confidence: 99%
See 1 more Smart Citation